Analysis of the efficacy of aspiration combined with venous sinus intraluminal thrombolysis for severe cerebral venous sinus thrombosis - ZHANG Jing; GE Han-ming; HAN Nan-nan; ZHANG Le-shi; LIU Zhi-qin; CHANG Ming-ze (Chinese Journal of Contemporary Neurology and Neurosurgery, 2025)
Objective To examine the safety and efficacy of catheter aspiration combined with microcatheter venous sinus intraluminal thrombolysis in the treatment of severe cerebral venous sinus thrombosis (CVST). Methods and Results We retrospectively analyzed the medical records of 10 patients with severe CVST who received catheter aspiration combined with microcatheter venous sinus intraluminal thrombolysis at The Affiliated Hospital of Northwest University, Xi'an No. 3 Hospital from January 2017 to December 2022. All 10 patients successfully completed the surgery. One patient achieved complete recanalization of the venous sinus immediately after the operation, 5 patients achieved partial recanalization, and 4 patients didn't recanalize. At the 90 d after the surgery, 5 patients achieved complete recanalization, 4 patients achieved partial recanalization, and one patient didn't recanalize. Among 7 patients who had intracranial hemorrhage (ICH) before the operation, head CT reexamination 7 d after the operation showed the hemorrhage at the original position was absorbed compared with that before the operation. Two patients developed newly ICH within 7 d after the operation. One patient experienced a poor prognosis [modified Rankin Scale (mRS) score of 3], while 9 had favorable prognosis (mRS ≤ 2) at 90 d after the operation. At the 12-month follow-up after the operation, all 10 patients had a favorable prognosis. Conclusions Catheter aspiration combined with microcatheter venous sinus intraluminal thrombolysis maybe a safe and effective treatment for severe CVST, showing improvement in prognosis.